Organic vegetable growers combine for market impact - Boateng, Osei K.; Keraita, Bernard N.; Akple, Maxwell Selase Kwasi (2007)
Like many Sub-Saharan African cities, Kumasi, in Ghana, has many farmers producing vegetables in and around the city. Often these farmers form associations and in Kumasi some of these associations have linked up to form bigger organisations that are now having an impact on the market. Osei Kwame Boateng, Bernard Keraita and Maxwell S.K. Akple report on the impact being made by the Gyinyase Organic Vegetable Growers' Association (GOVGA). GOVGA was formed by merging three farmers' organisations - Farmwell Organic Vegetable Growers' Association, Progressive Vegetable Growers' Association and Quarters Vegetable Growers' Association - from around the suburb of Gyinyase, which is about 10 km from the city centre. Formed in June 2006, it has 36 registered members, all of whom are fulltime commercial organic vegetable farmers. Farming is very intensive as each farmer holds an average of only 0.1 ha. Almost all lettuce, which is the most commonly grown vegetable in irrigated urban vegetable farming in Kumasi, comes from these sites. The other sites not represented by GOVGA mainly grow spring onions and cabbage.